2021
DOI: 10.51894/001c.25963
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on the Orthopaedic Surgery Residency Experience

Abstract: INTRODUCTION The rapid spread of the COVID-19 virus led to dramatic changes in graduate medical education and surgical practice. The purpose of this study was to evaluate the effects of the COVID-19 pandemic on Orthopaedic Surgery residency education in the United States. METHODS A survey sent to all residents of the 201 ACGME-accredited Orthopaedic Surgery programs in the United States. RESULTS A total of 309 Orthopaedic surgery residents responded to our survey. A subset of 283 (91.6%) residents surveyed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…As already mentioned, there are various studies investigating the effects of the COVID-19 pandemic on orthopaedics and traumatology residency training. One of those studies investigated the impact of the COVID-19 pandemic on orthopaedic surgery residency training in the United States and reported that the pandemic caused significant changes in the training experience of orthopaedic surgery residents, remarkably reduced clinical working hours and case volume, and led to worsening in such training [ 8 ]. A similar study conducted in India concluded that the COVID-19 pandemic adversely affected the academic training of residents, their surgical exposure and hands-on training [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…As already mentioned, there are various studies investigating the effects of the COVID-19 pandemic on orthopaedics and traumatology residency training. One of those studies investigated the impact of the COVID-19 pandemic on orthopaedic surgery residency training in the United States and reported that the pandemic caused significant changes in the training experience of orthopaedic surgery residents, remarkably reduced clinical working hours and case volume, and led to worsening in such training [ 8 ]. A similar study conducted in India concluded that the COVID-19 pandemic adversely affected the academic training of residents, their surgical exposure and hands-on training [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Orthopedic service was reduced to a minimum the capacity in outpatient clinics, inpatient wards, and elective surgeries. 9 , 13 , 14 Orthopedic surgery residents had to abandon a major part of their orthopedic practice and help caring for COVID-19 patients. On the other hand, directors of orthopedic training programs were put in a situation with which core orthopedic training falls incredibly under par.…”
Section: Discussionmentioning
confidence: 99%
“…The American Board of Orthopaedic Surgeons refers to this as a “transition from time-based programs for the acquisition of knowledge and skills to promoting competency-based curricula” [4]. The coronavirus-19 pandemic has also decreased surgical procedure volume for orthopaedic residents, which further emphasizes the need for better methods of teaching surgical skill [37]. Programs have reported various competency-based, novel methods of teaching such as the “surgical games,” in which residents complete simulated tasks, such as a cadaveric carpal tunnel release or a Sawbones model TKA, under direct observation by attending surgeons [16].…”
Section: The Argumentmentioning
confidence: 99%